La princesa and the pea - Elya, Susan Middleton, 1955-; Martinez-Neal, Juana; Andersen, H. C. (Hans Christian), 1805-1875. (New York, NY : G.P. Putnam's Sons, 2017)
"A rhyming twist on a classic fairy tale in which a queen places a pea under a young lady's mattress to see if she is truly a princess. Incorporates Spanish words and Includes a glossary"--
AD530L
Decoding demand: 53 (medium) Semantic demand: 93 (very high) Syntactic demand: 69 (high) Structure demand: 88 (very high)
Accelerated Reader AR
Pura Belpre Award (Illustrator), 2018.
2X2 Reading List, 2018
Keywords: Princes -- Juvenile fiction; Stories in rhyme -- Juvenile literature; Fairy tales -- Juvenile literature; Humorous stories -- Juvenile literature; Mothers and sons -- Juvenile fiction; Spanish language -- Vocabulary -- Juvenile literature; Peruvians -- Juvenile fiction; Pura Belpre Award winners; 2X2 Reading List, 2018.